CAN ENG 100 FOSTER ACADEMIC LITERACY? STUDENT PERCEPTIONS AT UNIVERSITY OF BUEA - Divine Nchang Ndimofor (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2026)
Academic literacy is essential for success in higher education, yet many undergraduate students struggle with academic writing, reading comprehension, communication, and critical engagement with texts. This study examined students’ attitudes and perceptions of the effectiveness of ENG 100 in developing academic literacy skills at the University of Buea. Specifically, it investigated students’ attitudes toward the course, perceptions of its effectiveness, its contribution to academic literacy development, teaching and assessment practices, and implementation challenges. Using a descriptive survey design informed by Academic Literacies Theory and the Theory of Planned Behaviour, data were collected from 200 undergraduate students through structured questionnaires. Quantitative data were analysed using frequencies and percentages, while qualitative responses were analysed thematically. Findings revealed generally positive attitudes and perceptions toward ENG 100, with students reporting improvements in academic writing, grammar, vocabulary, communication, reading comprehension, and overall academic performance. Teaching methods, lecturer feedback, and assessment practices were also viewed positively. However, challenges such as overcrowded classrooms, limited instructional time, inadequate learning resources, and insufficient practical writing activities constrained the course's effectiveness. The study concludes that ENG 100 significantly enhances academic literacy and recommends increased instructional time, improved learning conditions, better resource provision, and more learner-centred, practice-oriented instruction.